The phenotypic spectrum of Xia‐Gibbs syndrome - Yunyun Jiang; Michael F. Wangler; Amy L. McGuire; James R. Lupski; Jennifer E. Posey; Michael M. Khayat; David R. Murdock; Luis Sánchez‐Pulido; Chris P. Ponting; Fan Xia; Jill V. Hunter; Qingchang Meng; et al. (2018)
Xia‐Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT‐Hook DNA Binding Motif Containing 1 gene ( AHDC1 ). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.